Evaluasi Kerusakan Jembatan Dandu dalam Rangka Mendukung Kelancaran Transportasi Darat Ruas Soko-Sowominangun Kabupaten Lamongan - Titik Setya; Lily Oktavia (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The Dandu Bridge is one of the important infrastructures that functions as a land transportation link on the Suko-Sowominangun section, Lamongan Regency. The current condition shows that the bridge surface has suffered a lot of damage in the form of holes that can interfere with the smooth flow of traffic and endanger the safety of road users. Therefore, regular maintenance is needed so that the function of the bridge as a public facility remains optimal. One of the maintenance methods used is the Detailed Bridge Inspection Report (LPMJ), which aims to identify the condition of the bridge components as a whole. Field work practices carried out by students of the Lamongan Institute of Technology and Business in March-April 2025 are a means to understand the factors that cause damage. The results of the observation show that the damage is not only caused by structural factors, but also by non-structural aspects such as lack of awareness of road users and lack of communication with the surrounding community. Therefore, intensive education is needed for the community regarding the importance of maintaining the sustainability of the bridge's function, including the installation of proper traffic signs to minimize damage. In the LPMJ method, the upper structure components examined include floor plates, girders, and joints. Meanwhile, the lower structure includes pillars, abutments, and foundations. The bridge equipment that was observed included sidewalks, waterways, and railings. Maintenance should not only be focused on physical improvements, but also on social management that involves the active participation of the community, especially in areas with high traffic intensity. In conclusion, the maintenance efforts of the Dandu Bridge require an integrated approach that combines technical improvements and social empowerment, so that the sustainability of its function can be maintained for the long term.